What Role Do Masculine Norms Play in Men’s HIV Testing in Sub‑Saharan Africa?: A Scoping Review - Sileo, Katelyn M. (AIDS Behav, 2018)
Men living with HIV/AIDS in sub-Saharan Africa are less likely to test for HIV than women. We conducted a scoping review in May of 2016 to identify how masculine norms influence men’s HIV testing in sub-Saharan Africa. Our review yielded a total of 13 qualitative studies from 8 countries. Masculine norms create both barriers and facilitators to HIV testing. Barriers included emotional inexpression, gendered communication, social pressures to be strong and self-reliant, and the fear that an HIV positive result would threaten traditional social roles (i.e., husband, father, provider, worker) and reduce sexual success with women. Facilitators included perceptions that HIV testing could restore masculinity through regained physical strength and the ability to re-assume the provider role after accessing treatment. Across sub-Saharan Africa, masculinity appears to play an important role in men’s decision to test for HIV and further research and interventions are needed to address this link.